2020
DOI: 10.1016/j.carbon.2020.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-size diamond seeding for low-thermal-barrier growth of CVD diamond onto GaN and AlN

Abstract: We report a method of growing a diamond layer via chemical vapour deposition (CVD) utilizing a mixture of microdiamond and nanodiamond seeding to give a low effective thermal boundary resistance (TBReff) for heat-spreading applications in high-frequency, high-power electronic devices. CVD diamond was deposited onto thin layers of both GaN and AlN on Si substrates, comparing conventional nanodiamond seeding with a two-step process involving sequential seeding with microdiamond then nanodiamond. Thermal prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…This results in an extremely rough surface that increases the scattering of the phonons. Smith et al [76] and Waller et al [74] reported TBR GaN/diamond as high as 220 m 2 •K/GW. In both works the GaN surface was seeded using a two-step electrostatic spray technique (see more details in Section 4.1.3.1).…”
Section: Decreasing Thermal Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in an extremely rough surface that increases the scattering of the phonons. Smith et al [76] and Waller et al [74] reported TBR GaN/diamond as high as 220 m 2 •K/GW. In both works the GaN surface was seeded using a two-step electrostatic spray technique (see more details in Section 4.1.3.1).…”
Section: Decreasing Thermal Stressmentioning
confidence: 99%
“…At the same time the bottleneck of the heat extraction was recognized to be the TBR between GaN and diamond (TBR GaN/diamond ) [72] and most of following research focused on decreasing it, whether by decreasing the dielectric thickness, by using a different dielectric, or by optimizing the diamond nucleation layer [10,[72][73][74][75][76][77][78][79][80][81][82][83][84]. The impact of the thickness of the GaN buffer layer on the R th of the HEMT devices [85][86][87][88][89][90] and the effects of the stress caused by the difference in the CTEs of GaN and diamond [91][92][93][94][95][96] were also evaluated by different research groups.…”
Section: Gan-on-diamondmentioning
confidence: 99%
See 1 more Smart Citation
“…The interface thermal properties between GaN and NCD diamond were improved by Smith et al using a two-step mixed-seeding method [86]. It was found that the mixture of microdiamond and nanodiamond seeding led to a low TBR eff .…”
Section: Diamond Epitaxially Grown On Gan Wafersmentioning
confidence: 99%
“…This results in an expansion of the surface of GaN substrate; the irregular topography of the substrate significantly increases the adhesion of the diamond layer to the GaN surface. This is critical due to cooling cracks or small gaps opening up at the diamond/GaN interface, resulting in partial or full delamination and negligible thermal conduction through the interface, which was shown by Smith et al [ 10 ]. In view of the fact that the lack of a covalent bond between Ga-C can lead to delamination of the diamond layer, solutions that increase the adhesion of the layer to GaN are very desirable.…”
Section: Introductionmentioning
confidence: 99%